ASSOCIATION BETWEEN IT-HOSPITAL MORTALITY AND NON-SURGICAL COMPLICATIONS AFTER OPERATION IN LOWER LIMB AMPUTATION DUE TO PERIPHERAL ARTERY DISEASE - Денис Николаевич Макаров; Елена Михайловна Васильченко (Медицина в Кузбассе)
Objective – to investigate the structure of non-surgical complications after operation, define its effect on in-hospital mortality in lower limb amputations in patients with peripheral artery disease.